Auriculoterapia na redução da ansiedade em trabalhadores da saúde da atenção primária - Trindade, Terezinha Paes Barreto (2023)
Auriculotherapy has emerged as an Integrative and Complementary Health Practice and one of its clinical indications is anxiety control. The study aimed to evaluate the effects of auriculotherapy and understand the perception of Primary Healthcare workers about auriculotherapy. This is a descriptive study, with a mixed approach and quasi-experimental design - cause-effect intervention in a single group. We included 14 workers from a Family Health Unit in a capital city of northeastern Brazil. The data was collected between January 2022 and January 2023 and the collection was developed in stages: the participants answered The State-Trait Anxiety Inventory (IDATE-Trait), Pain Scale (EVA), quality of life questionnaire - WHOQOL-bref, socioeconomic data and an open question about the use of auriculotherapy; then underwent 10 weekly sessions of auriculotherapy and again answered the same instruments and the open question, except the sociodemographic data; 15 days break without therapy; application of the same instruments used at the end of the first stage, 10 more therapy sessions and reapplication of the instruments; interviews with 9 of the participants. The interviews were recorded and transcribed in full to understand and highlight the auriculotherapy treatment. For qualitative data analysis we adopted the Content Analysis with thematic approach, according to Bardin (2016). In the Statistical analysis used the software Statistical Package of the Social Sciences 21.0 (SPSS, Inc., Chicago, IL, USA). For the quantitative results, Wilcoxon's test and t-test were used, considering the significance level of 5%. We observed improvement in quality of life (general WHOQOL-bref score), considering before and after the therapeutic phases 1 versus 2 (p=0.007) and 3 versus 4 (p=0.036). As for the IDATE-T, there was a significant difference in the reduction of anxiety in phase 3 versus 4 (p=0.036). The EVA scale results were not statistically significant. In the qualitative results, reports demonstrated therapeutic effects on sleep improvement, physical and mental relaxation, anxiety and stress reduction; also reports of satisfaction, credibility, and adherence to therapy. The participants' narratives also emphasized the importance of the therapist and in the listening, humanization, and welcoming of the demands brought. Listening guided the practice of auriculotherapy and the therapist's speech during the care process using auriculotherapy as an alternative care tool for the caregiver in health. It is important to implement auriculotherapy and other Integrative and Complementary Practices in all Primary Healthcare, strengthening the National Policy for Integrative and Complementary Health Practices.